Vietnam Public Expenditure Review in the Period of 2007-2017 and Some Recommendations - Khac Lich, Hoang; Huyen, Nguyen Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
This study explores the current situation of public spending of Vietnam in the period from 2007 to 2017. The results show that the total state budget expenditure has increased over the past 10 years; however the growth rate of public expenditure has reduced. The state budget deficit and the ratio of public debt to GDP have remained at a high level. The analysis also indicates that there has been an increase in the proportion of recurrent spending in total state budget expenditure. By constract, the percentage of investment expenditure tends to decrease. Expenditures on health, education and science and technology have risen in recent years.